Postkritična praksa in interpretacija književnosti - Latković, Ivana (Slavistična revija, 2020)
In light of the humanities' current emphasis on pluralism of research methods and perspectives, this article presents a post-critical approach and methodology and posits their relevance in the study of literature. Starting with Rita Felski's theses and with a brief overview of the contributions of other participants in postcritical practice (Christopher Castiglia, Matthew Mullins), special attention is paid to the topic of literary interpretation-i.e., the assumptions of its interpretation in this research perspective-"suspicious interpretation" / "opening to the text", "hypercritical analytical style" / "affective hermeneutics," "pleasure of criticism" / "pleasure of reading," etc.
Keywords: Felski, Rita; interpretacija; kritika; metodologija; prakse branja; preučevanje književnosti